Financiamento público à indústria de exibição cinematográfica: um estudo de caso no Brasil - Goldemberg, Diana (2014)
This study aims to evaluate the impact of new credit lines to Brazilian movie exhibition industry, one of the existing forms of government support for this sector. The evaluated disbursements, conducted by the Brazilian Development Bank (BNDES), from 2007 to 2012, consist of long-term credit for opening new screens, with below-market interest rates and a flexible collateral structure. The econometric methodology used is the Synthetic Control Method, as formalized by Abadie et al. (2010). Under this method, it was not possible to identify any positive contribution of the credit policy after comparing the individual performance of the exhibitors who received the credit versus their synthetic controls, nor on the evolution of the number of screens nor on admissions. Furthermore, a possible aggregate effect was tested, considering the evolution of the Brazilian number of admissions per capita, also with no positive contribution of the policy being identified.